2008
DOI: 10.1111/j.1440-1584.2008.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a community pharmacy‐based rural asthma management service

Abstract: These results indicated that the community pharmacy-based RAMS model can improve asthma outcomes for patients in rural settings, and similar models for asthma and other chronic diseases should be tested rigorously and adopted in rural primary care practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 16 publications
1
39
0
1
Order By: Relevance
“…These results therefore provide an important benchmark to practices in different parts of the world. These outcomes reinforce other findings that pharmacists, who already interact with patients as they fill their prescriptions, are well suited not only to provide regular education and counseling, but also to help correct patients' misconceptions about their condition and medications, thereby encouraging self-management practices that support better outcomes [37][38][39][40][41][42][43][44][45][46][47][48][49]. Thus, arranging regular and repeated guidance by pharmacists through outpatient services would be valuable for asthma patients.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results therefore provide an important benchmark to practices in different parts of the world. These outcomes reinforce other findings that pharmacists, who already interact with patients as they fill their prescriptions, are well suited not only to provide regular education and counseling, but also to help correct patients' misconceptions about their condition and medications, thereby encouraging self-management practices that support better outcomes [37][38][39][40][41][42][43][44][45][46][47][48][49]. Thus, arranging regular and repeated guidance by pharmacists through outpatient services would be valuable for asthma patients.…”
Section: Discussionsupporting
confidence: 79%
“…While studies of asthma education often involve nurses or doctors (shown to be equally effective [36]), many have shown the efficacy of using pharmacists in the community setting [37][38][39][40][41][42][43][44][45][46][47][48][49]. A recent study by Petkova [37] reported on a 4-month educational intervention based in community pharmacies.…”
Section: Discussionmentioning
confidence: 95%
“…Pharmacist interventions have been shown to improve asthma control, asthma knowledge and self-care in disease management [26,33,34]. Different approaches to asthma education delivery have now been tested in pharmacies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted proved that pharmaceutical care provided by a pharmacist is an important part in the asthma management. [35678910111213] Use of drugs in asthma patients is also a matter of self-regulation and self-management. [14] This study aims at the outcome of providing pharmaceutical care for asthma patients through an active partnership between clinical pharmacist and patients, for achieving a good control of asthma with symptom monitoring, optimal pharmacotherapy, and control of confounding factors.…”
Section: Introductionmentioning
confidence: 99%